RESULTS OF THE APPLICATION OF ADDENBROOKE’S REVISEDCOGNITIVE TEST EVALUATIONS: COMPARISON OF TWO CASE REPORTS - Tanja Todorović (STED Journal)
The ACE-R is a widely accepted instrument in clinical practice, the revisions of which have been overcome certain weaknesses. The aim of this paper was to present the results of the ACE-R test research, and to analyze and compare the results obtained in the work with a healthy subject and a clinical subject diagnosis. The respondents are of similar age and similar characteristics. Selected from the clinical population is a respondent with a diagnosis of depression after a stroke, which is the most common a complication of the same. The results obtained in this paper partially confirmed the results of the previous ones research. The application of the mentioned test showed that the two respondents differed in their views measured abilities: the subject with a diagnosis of depression produces difficulties in recognizing tasks material, and verbal fluency and visuospatial abilities are reduced compared to healthy the respondent.